Konsep Pembaruan dalam Islam Perspektif Muhammad Abduh - Nur Wahyudi, Mohamad; Zaenab, Siti (Alhamra Jurnal Studi Islam, 2023)
The history of revival in Islamic civilization can be marked since the Middle Ages, but towards the end of the Middle Ages Islam experienced a very significant setback. This setback occurred due to several things, one of which was in the field of religion, the religion which was supposed to provide values for its adherents was used as a tool of legitimacy for the authorities. In addition, Ulama’ as holders of authority or religious stakeholders are often involved in the competition between madhhabs so that it has an impact on their adherents, namely the fanaticism of madhhabs, besides the jumud nature that occurs among Muslims in this case also contributes to making the stigma of Islam become increasingly backward and these are a few pictures of the historical reality surrounding the life of a Muhammad Abduh at that time. Meanwhile, in this study, the author uses the Library Research method, which means examining the thoughts of the character by providing a critical analysis of his thoughts. The results of this study indicate that in some respects Abduh’s ideas can be said to be still relevant, especially regarding the attitude of religious people who are difficult to open up and tend to justify religion for the interests of their respective groups.